Assessment of Oral Hygiene Practices and the Factors Influencing Selection of Tooth and Interdental-Cleaning Devises: A Cross Sectional Survey of Pakistani Adults - Tahira Hyder, Ayesha Saghir Butt, Saima Quraeshi, Asfia Anwar, Sara Rahman (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The current study aimed at determining and characterizing the oral hygiene habits and behaviors of a subset of Pakistani population seeking dental care at a private hospital in Karachi. Study Design: Cross-sectional survey. Place and Duration of Study: The study was conducted in the department of Oral Medicine and Diagnosis in Dental Out-Patient-Department of Ziauddin University Karachi from January 2022 to July 2022. Methodology: A total of 530 adult males and females who visited Ziauddin Dental Out-patient-department (OPD) were recruited using non-probability consecutive sampling, as a representative sample of the Pakistani population. After obtaining an informed consent, interviews using a structured questionnaire were conducted. Data analysis was performed with SPSS version 22. Results: The majority of the subjects interviewed (58.3%) use toothbrush, while 5.8% use miswak, 23.2% use both toothbrush and miswak, and 5.5% use their fingers to clean their teeth. There was no significant difference in selection of oral hygiene device between genders, age groups, level of education, and social economic status. To clean interdental areas, majority participants use toothpicks (39.6%), 13.4% use dental floss, 4.5% use interdental brush while 34.1% use none. 14.3% of the participants reported that they use a mouth-rinse. Conclusion: An assessment of oral hygiene practices serves as a guide for designing effective health education programs that fulfils the periodontal requirements of the target population. Efforts should be made to promote the correct brushing techniques and timings and implement the usage of interdental cleaning aids. Keywords: dental health education, miswak, toothbrushing, floss, mouth rinse